2017
DOI: 10.1371/journal.pone.0181433
|View full text |Cite
|
Sign up to set email alerts
|

PrEP in Italy: The time may be ripe but who's paying the bill? A nationwide survey on physicians' attitudes towards using antiretrovirals to prevent HIV infection

Abstract: Several studies have demonstrated the efficacy of the oral pre-exposure prophylaxis (PrEP) with tenofovir (with or without emtricitabine) on preventing HIV-negative partners of HIV infected patients to become infected through sexual contacts. PrEP is already available in the United States and now is approved by European Medicine Agency. In this setting we would like to gauge physicians’ knowledge, acquaintance with and attitude to include PrEP in their clinical practice. A cross sectional survey was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…These findings are consistent with the results of an Italian study, which showed that, despite 98% of specialized doctors were aware of PrEP, only 14% of them had previously suggested or prescribed PrEP to their patients [ 15 ]. Another Italian study showed that, among physicians expert in antiretroviral therapy, almost 50% of them believed that there are insufficient reasons to make PrEP available in Italy [ 38 ]. However, PrEP efficacy and safety have been confirmed by a steadily growing body of evidence [ 5 , 6 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the results of an Italian study, which showed that, despite 98% of specialized doctors were aware of PrEP, only 14% of them had previously suggested or prescribed PrEP to their patients [ 15 ]. Another Italian study showed that, among physicians expert in antiretroviral therapy, almost 50% of them believed that there are insufficient reasons to make PrEP available in Italy [ 38 ]. However, PrEP efficacy and safety have been confirmed by a steadily growing body of evidence [ 5 , 6 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the third section, knowledge, attitudes and practices regarding PrEP were investigated (items [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. This part of the questionnaire was preceded by a brief definition of PrEP, in order to establish a common ground for each respondent in answering these questions, hence increasing results comparability.…”
Section: Questionnairementioning
confidence: 99%
“…Data on PrEP knowledge, though not further assessed, are consistent with previous results among Italian HIV specialists [ 15 ]. Among patients, discussion with their HIV physician was reported by 15%, though we excluded this item from the MLR analysis as in Italy we had observed conflicting results regarding attitudes towards PrEP prescription among HIV physicians [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study used a clinical case to illustratethe use of PrEP. Another study by Di Biagio et al [18] was conducted in Italy, a European country in which the use of PrEP based on tenofovir and emtricitabine has not yet been approved, although in Europe, it already has the approval of the European Medicine Agency. In this study, the responses to a 21-item survey conducted among physicians at Italian centres that treat HIV patients, was analysed.…”
Section: Resultsmentioning
confidence: 99%